UNITY OF SCIENCE AND ISLAM AT UIN WALISONGO SEMARANG AND SULTAN AGUNG ISLAMIC UNIVERSITY, AND THEIR RELATIONSHIP WITH RELIGIOUS MODERATION - Abdurrahman Mas’ud; Mochamad Munawar Said Munawar Said; Noor Amalia Chusna (Balai Penelitian dan Pengembangan Agama Jakarta, 2022)
The development of science and Islam gave birth to harmonious and dialogical relationships that complement each other. The existence of Islamic Religious Colleges (PTKI) has a primary function in maintaining, developing, and growing the whole person. Alignment of Islamic values ​​and general knowledge competence is a challenge faced by State PTKI and Private PTKI in developing general study programs. The development of the general curriculum in the syllabus of the State PTKI (UIN Walisongo Semarang) and the Private PTKI (Sultan Agung Islamic University) is worthy of study. This study aims to determine and evaluate the context of the existence of general study programs, the learning process, and aspects of the product results contained in UIN Walisongo Semarang and Sultan Agung Islamic University. The methodology used is descriptive qualitative with a context, input, process, product (CIPP) evaluation model. The results of the evaluation on the analysis of the CIPP method show that the general study programs at UIN Walisongo Semarang and the Islamic University of Sultan Agung have had a mature context, supporting input factors. These processes run optimally, and can produce products in the form of good graduates. How is the paradigm of the unity of science at PTKI State and Private, deeper seen from the perspective of religious moderation? How is the direction of Islamic universities. Still moderate in the future?